The relationship between reading mastery and factual text comprehension among form one students in the rural area - Shelen Aderina Kok (2007)
The main purpose of this survey is to identify reading and text comprehension ability based on the level of free reading, guided and frustration. It is also done in order to identify if there is a connection between the mastery of reading and comprehension with students' performance in reading and comprehension. The survey subject consists of 60 Form one students, 30 boys and 30 girls. The experiments were held by using descriptive observation. Information and data gathered by using 4 observation instruments, which comprises profile form, the reading passage of factual text (Individual reading transcription recorded), text comprehension and a set of questionnaire to obtain responses from teachers regarding reading and comprehension skills. All experimental data would be analysed by using proportion per hundred and programmed of Statistical package for Social Science (SPSS) that is Simple Regression statistical analysis. The result of the survey shows a significant relationship between students' mastery in reading and comprehension with their overall performance in reading and comprehension at the value 0.016, p<0.05, that is p=0.016. The discovery of this survey suggests that English teachers need to give appropriate attention to ensure the mastery of both reading and text comprehension skills by keeping students interested in reading through appropriate approaches, methods and technique. However, in order to ensure the effectiveness of reading text comprehension learning, cooperation among the administrator, teachers and students is crucial.